Literature Review: Benefits and applications of alginate liase enzyme) - Sirwati, Fadila; Putri, Dwi Hilda; Rachmayati, Rike (Bioscience, 2024)
Alginate is a polymer found in large amounts in the cell walls of brown algae. This polymer consists of α-L guluronic acid (G) and mannuronic acid (M). Alginate can be degraded by an enzyme, known as alginate liase by removing the glycosidic bond and producing an unsaturated oligosaccharide with a double bond at the non-reducing end. To provide an overview of the utilization of alginate lyase, information is needed on the biological activity of alginate lyase as an antibiofilm agent, the production of alginate oligosaccharides, and its antioxidant properties. This study aims to provide scientific insight into the important role of the benefits and applications of alginate lyase. The research design used was a literature review. Articles were collected based on sources from PubMed, Science Direct, and Google Scholar, which included more than thirty national and international journals. The articles collected showed that alginate lyase exhibits many biological activities, including antibiofilm, antioxidant, and oligosaccharide production. These properties have the potential to be used in a wide range of applications, which include the food, pharmaceutical, and biotechnology industries.